Pediatric insomnia in Unani system of medicine: A pilot narrative review - Nazia Anjum; Md. Sohail (Traditional Medicine and Modern Medicine)
Pediatric insomnia, referred to as “Sahar” in the Unani System of Medicine, is a common sleep disorder that adversely impacts children’s physical, emotional, and cognitive development. This condition typically manifests as prolonged wakefulness, restlessness, and challenges in sleep initiation and maintenance, often influenced by environmental, behavioral, and biological factors. This pilot review aims to examine the concept of pediatric-specific insomnia through the lens of Unani Medicine, by synthesizing insights from its three classical texts and two pediatric treatises. The analysis identifies several causes of insomnia, including the consumption of unwholesome milk, environmental factors such as dryness, and emotional disturbances. Unani Medicine emphasizes the significance of temperamental imbalances and dietary practices as core contributors to sleep disturbances. Recommended management strategies encompass dietary modifications, herbal remedies like Poppy (Papaver somniferum) and Lettuce (Lactuca sativa), as well as behavioral interventions such as soothing oil massages and engaging children with pleasant sounds. This exploration offers valuable insights into pediatric insomnia and presents natural treatment alternatives that can complement conventional approaches. Further research is essential to validate the safety and efficacy of these traditional remedies in clinical practice.